Observing the Ice‐Covered Weddell Gyre With Profiling Floats: Position Uncertainties and Correlation Statistics. Issue 11 (22nd November 2018) - Chamberlain, Paul M.; Talley, Lynne D.; Mazloff, Matthew R.; Riser, Stephen C.; Speer, Kevin; Gray, Alison R.; Schwartzman, Armin
Abstract: Argo‐type profiling floats do not receive satellite positioning while under sea ice. Common practice is to approximate unknown positions by linearly interpolating latitude‐longitude between known positions before and after ice cover, although it has been suggested that some improvement may be obtained by interpolating along contours of planetary‐geostrophic potential vorticity. Profiles with linearly interpolated positions represent 16% of the Southern Ocean Argo data set; consequences arising from this approximation have not been quantified. Using three distinct data sets from the Weddell Gyre—10‐day satellite‐tracked Argo floats, daily‐tracked RAFOS‐enabled floats, and a particle release simulation in the Southern Ocean State Estimate—we perform a data withholding experiment to assess position uncertainty in latitude‐longitude and potential vorticity coordinates as a function of time since last fix. A spatial correlation analysis using the float data provides temperature and salinity uncertainty estimates as a function of distance error. Combining the spatial correlation scales and the position uncertainty, we estimate uncertainty in temperature and salinity as a function of duration of position loss. Maximum position uncertainty for interpolation during 8 months without position data is 116 ± 148 km for latitude‐longitude and 92 ± 121 km for potential vorticity coordinates. The estimated maximum uncertainty in local temperature and salinity over the entire 2, 000‐m profiles during 8 months without position data is 0.66  ∘ C and 0.15 psu in the upper 300 m and 0.16  ∘ C and 0.01 psu below 300 m. Plain Language Summary: Argo‐type profiling floats do not receive GPS positioning while under sea ice. Current common practice is to approximate the unknown position by linearly interpolating between the known positions before and after ice cover. This linear interpolation is not the true path that these floats follow with under the ice. What is the uncertainty of this linear approximation? Float position and velocity decorrelate with time—meaning the linear approximation of position tends to be worse as time increases. In our paper, we address the question of measurement uncertainty as a function of time by breaking the problem into two pieces: the position uncertainty as a function of time and the measurement uncertainty as a function of position. Combining these statistics, we estimate uncertainty as a function of time of position loss for temperature and salinity as well as surface fluxes derived from the Southern Ocean State Estimate. Key Points: Argo float position uncertainty when lost under sea ice for 8 months was found to be on the order of 100 km Mapping error in salinity and temperature due to 8 months of position loss was found to be 0.15 psu and 0.66 degrees C in the upper ocean Mean RMS difference of surface heat and salinity flux between true and interpolated float trajectories was 28.5 W/m 2 and 1.8 × 10 −3 kg·m −2 ·s −1